Designing amplifier circuits - Feucht, Dennis (Feucht, Dennis. Analog circuit design series, 2010)
Design is a creative activity that begins with a definition of the problem to be solved or specification of the device to be built. Solving the problem or specifying the device in enough detail to build it is the goal of the designer. Usually more than one alternative solution or design is possible. Sometimes they are already known, and the problem consists mainly in adapting a known general solution to a particular application for it. This is 'standard engineering' practice. Other problems have no known solution and require a novel search, which can include novel adaptation of existing solutions to similar problems. This is 'state-of-the-art' engineering, sometimes called engineering research and development (R&D). When a solution is found, it is then refined and specified for use.